My teacher gave me this problem:

\(a\), \(b\) and \(c\) are three positives such that \(abc = 1\). Prove that

\[\large M = \dfrac{1}{a^2 - a + 1} + \dfrac{1}{b^2 - b + 1} + \dfrac{1}{c^2 - c + 1} \le 3\]

Here's how I solve it.

\[\large \begin{align} M &= \dfrac{1}{a^2 - a + 1} + \dfrac{1}{b^2 - b + 1} + \dfrac{1}{c^2 - c + 1}\\ &= \left(a + 1 - \dfrac{a^3}{a^2 - a + 1}\right) + \left(b + 1 - \dfrac{b^3}{b^2 - b + 1}\right) + \left(c + 1 - \dfrac{c^3}{c^2 - c + 1}\right) && m^3 + 1 = (m + 1)(m^2 - m + 1)\\ &= (a + b + c) - \left(\dfrac{a^2}{bc + a - 1} + \dfrac{b^2}{ca + b - 1} + \dfrac{c^2}{ab + c - 1}\right) + 3 && abc = 1\\ &\le (a + b + c) - \dfrac{(a + b + c)^2}{(ab + bc + ca) + (a + b + c) - 3} + 3 && \text{Sedrakyan's inequality, Engel’s form or Titu’s lemma}\\ &\le (a + b + c) - \dfrac{(a + b + c)^2}{\dfrac{(a + b + c)^2}{3} + (a + b + c) - 3} + 3 && ab + bc + ca \le a^2 + b^2 + c^2\\ \end{align}\]

(Fun fact, the Sedrakyan's inequality is called the Schwarz inequality here.)

Let \(a + b + c = n\), we have that \(a + b + c \ge 3\sqrt[3]{abc} = 3\) and \(M \le n - \dfrac{3n^2}{n^2 + 3n - 9} + 3\).

The problem becomes:

Calculate the maximum value of the following expression if \(n \ge 3\).

\[\large M' = n - \dfrac{3n^2}{n^2 + 3n - 9} + 3\]

So if you can:

solve the next part of the solution

(prove that there is no maximum value of \(M'\) and) solve the original problem in a faster, more convenient way

then feel free to write them in the comments' section. Please help me!

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestWell, the expression is in one variable 'n' and also, we know from the given condition of abc=1 that a+b+c = n is atleast 3......(AM-GM)........Now, by simple first derivative,we see that the expression in M is always increasing for n>=3..........And hence, the maximum value of M is 3 which occurs when n = 3 or a+b+c=3 or a=b=c=1.........!!! Here is a graph supporting the answer..........

Also, my approach was on the same lines as yours........I usually try to reduce inequalities to a single variable, just like you have done.....!!

Log in to reply

I am really sorry but I am just in grade 9 so I can't use derivatives, I hope that you can come up a solution completely in pure algebra.

Log in to reply

Care to elaborate? I don't see the connection between the Desmos graph and the inequality posed.

Log in to reply

Here Sir, I have added the inequality of the derivative, showing the region where the function is increasing...........Hope it is clear now......:)

Log in to reply

Your first statement claims that \(M\) has no upper bound. But your second statement says it has an upper bound of 3. How is that possible?

Log in to reply